Additive Expression of hTBM on hCD46 Stable Cell Line Has Synergistic Effect on Complement Regulation. (July 2018) - Kim, Hwajungh; Hurh, Sunghoon; Lee, Sun-Kyung; Lee, Yoo Jin; Hwang, Jong-Ik; Lee, Byeong Chun; Yang, Jaeseok; Ahn, Curie
Abstract : Background: Coagulation dysregulation and intravascular thrombosis during acute humoral xenograft rejection (AHXR) still remains the major obstacle in solid organ xenotransplantation. TBM or CD46 have been reported as an anti-coagulant or complement regulatory molecules and also potent anti-inflammatory molecules. In this study, we showed whether additional TBM expression on CD46 stable cell has synergistic effects on anti-coagulant or complement regulation. Methods & Results: Fetal pig fibroblasts were transfected with hTBM-hCD46 vector and colonies expressing high amounts of the fusion protein were selected and used as nucleus donor for somatic cell nuclear transfer (SCNT) and three gilts became pregnant and one farrowed one live male piglet, which was no healthy and moved to the SPF facility but died one day after and two of the pregnant gilts, however, aborted during gestation. We isolated fibroblast from the ear of TG pig expressing hTBM-hCD46 and check the expression levels of each genes and the regulatory functions on complement and coagulation. Serum toxicity was significantly reduced in the fibroblast from hTBM-hCD46 TG pig compared with wild type pig's fibroblast at 10% or 20% serum treatment. Thrombin generation was dramatically reduced and coagulation time was prolonged in the fibroblast from hTBM-hCD46 TG pig compared with wild type pig's fibroblast. Conclusion: The fibroblast from hTBM-hCD46 TG pig has synergistic effects on anti-coagulant or complement regulation therefore, genetically modifying pigs expressing TBM and CD46 would be a promising candidate for xenotransplantation to prolong the graft survival.